• 1)3sin²π÷2-4tg²π÷4-3cos²π÷6+3ctg²π÷2
    2)tg5π÷4×sinπ÷3-cos7π÷6×sin3π÷2
    3)sinα=3÷4,0≤α≤π÷2
    4)ctgα=2÷3,π≤α≤3π÷2
    5)ctgα-cosα-1÷sinα
    6)(sinβ×ctgβ)²+(cosβ×tgβ)2

Ответы 1

  • 1)3*1²-4*1²-3*(√3/2)²+3*0²=3-4-2,25+0=-3,252)1*√3/2-(-√3/2)*(-1)=√/2-√3/2=03)sina=3/4,0≤a≤π/2a=arcsin3/44)ctga=2/3,π≤a3π/2a=π+arcctg2/35)ctga-(cosa-1)/sina=cosa/sina -(cosa -1)/sina==(cosa-cosa+1)/sina=1/sina6)(sinb*ctgb)²+(cosb*tgb)²=(sinb*cosb/sinb)²+(cosb*sinb/cosb)²==cos²b+sin²b=1
    • Автор:

      blasts4co
    • 5 лет назад
    • 0
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years